MILLENNIAL GENERATION INTERESTING FACTORS IN THE PROCESS OF DEVELOPING CHARACTERS OF PANCASILA DURING ONLINE LEARNING - Angelina, Sabela Ayu (Ganesha Civic Education Journal, 2024)
Determining Factors of the Millennial Generation in Running a Country and Good Character Education. Currently hit by the Covid-19 pandemic, changes in government regulations, namely implementing online learning at home, must be carried out by students. The purpose of writing this article is to determine the inhibiting factors for the millennial generation in carrying out online learning during the Covid-19 pandemic, both from normal and abnormal students. Method: The method used is a literature review. Data collection techniques using Google Scholar and Mendeley with a limit of 2019 to 2021. This study focused on the keywords "millennial generation", "character", and "online learning". The results of the study were obtained from ten articles that the obstacles felt by the millennial generation significantly affect their negative character. The millennial generation has obstacles that they often experience, namely not having a smartphone, limited internet quota, unstable internet network, inadequate technology, inadequate facilities and infrastructure, minimal understanding of IT, lack of interest in learning, less supportive family environment, and lack of parental guidance so that solutions are needed from both the government and other parties. The implications of the research are the optimization of the use of Learning Management System (LMS), social media, or collaborative applications to convey Pancasila values. This means that educators need to be more technology literate and develop creativity in utilizing digital features for character education purposes.